Matching approach for UHF RFID tag antenna immersed in dielectric materials. (June 2020) - Sarsri, Nadir; Myllymäki, Sami; Sonkki, Marko; Srifi, Mohamed Nabil
Abstract: In this paper, a novel UHF RFID Tag antenna for automotive tire is presented. The antenna shape and size are reduced by using a meander line. To ensure a proper impedance matching between the antenna and the microchip, especially when antenna is immersed in dielectric medium, a simple approach is presented. The square-load is added at the both ends of antenna tag in order to improve the bandwidth aspect. The tag has a reduced size: 40mm*13.5mm*0.018mm. Hence, it can be embedded in automotive tire. The tag provides the low profile and low cost fabrication. The simulated results show that our approach is helpful to achieve impedance matching process. Moreover, the proposed antenna has omnidirectional radiation patterns and a good gain that satisfy maximum power transmitting in RFID communication once tag is embedded in rubber material.